Evaluasi Analisis Pont dan Howes pada Model Studi Mahasiswa Angkatan 2022 dan 2023 pada Ras Deutro Melayu di Fakultas Kedokteran Gigi Universitas YARSI - Devita Syahfitri; Nugroho Ahmad Riyadi; Toto Heriyanto (YARSI Dental Scientific Meeting - e Journal, 2026)
Background: Study model analysis is a tool to establish diagnosis and treatment planning in orthodontics, one of the analyses is Pont and Howes analysis. Objective: This study aims to evaluate Pont and Howes analysis in students of the 2022 and 2023 classes of Deutro Melayu race at the Faculty of Dentistry, YARSI University. Method: This study was conducted on 53 study models consisting of 28 students of the 2022 class and 25 students of the 2023 class. The study models were measured for Pont and Howes analysis then the data were processed with One Sample T-Test Independent and One Sample Non-Parametric tests. Results: The results of the Pont analysis showed a premolar index of 38.52 ± 4.90 and a molar index of 48.15 ± 6.12 smaller than the standard Pont value (premolar index 80 and molar index 64). While the Howes analysis was 39.93% smaller than the standard Howes value (44%). This study shows a statistically significant difference between the Pont and Howes values due to racial and ethnic differences in the study population. Conclusion: The Pont and Howes analyses in this study are smaller than their respective standard values. The use of Pont and Howes analyses in Islam is considered permissible (mubah) or recommended (mandub) and is considered an act of worship when based on the intention to improve the quality of dental health services and develop beneficial knowledge.